MORPHOFUNCTIONAL CHARACTERISTICS OF NEURONS OF THE CA1 ZONE OF THE HIP-POCAMPUS AFTER THE CHRONIC ALCOHOL INTOXICATION AND WITH THE BACKGROUND OF THIOL ANTIOXIDANTS IN RATS - Belenichev, I.F.; Kucher, T.V.; Kuzo, N.V. (World of Medicine and Biology, 2016)
Development of new methods of the neuroprotection is an important task of the modern pharmacology. In current study we assessed the neuroprotective activity of thiol antioxidants (TO) such as thiocetam, heptral, and N-acetylcystein in terms of their influence on morphofunctional indices and apoptosis of neurons of the CA-1 zone of hippocampus in experimental animals. Study performed on 40 white mongrel male rats with weight of 160-180 grams, which were treated with intragastric instillation of ethanol according to the scheme: 10 days – 15 % solution with dose of 4 g/kg, next 10 days – 15% solution with dose of 6 g/kg and last 10 days – 25% solution with dose of 4 g/kg.